The COVID-19 pandemic intensified resource conflicts and indigenous resistance in Brazil. (February 2021) - Menton, Mary; Milanez, Felipe; Souza, Jurema Machado de Andrade; Cruz, Felipe Sotto Maior
Highlights: A history of territorial struggles strengthened the ability of some groups of indigenous peoples in Brazil to combat COVID-19. Indigenous led self-protection and resistance counter government 'politics of extermination' and 'genocide by omission'. Strategies included: self-isolation and blockades, social media campaigns and fundraising, and court cases against the government. Despite violence and repression, the indigenous movement has grown and is better positioned to fight the pandemic than it was a decade ago. Abstract: Indigenous peoples in Brazil have suffered disproportionately from the COVID-19 pandemic due to limited access to an already precarious public health system together with continued attacks on their cultures, their territories and their way of life. These attacks come as part of the government's attempts to further neoliberal development and undermine environmental and indigenous rights, taking advantage of what the Minister of Environment called 'a moment of calm while the press is focusing on the pandemic'. The pandemic has intensified environmental conflicts affecting indigenous peoples, both in amplifying conflicts but also in sparking new acts of resistance and self-protection of indigenous lives and territories. Based on case studies and monitoring of rapidly evolving social media and WhatsApp posts, we analyse these processes through a political ecology lens. We find confirmed cases and deaths amongst indigenous peoples centred around tourism hotspots, mining sites, and other development projects. Yet the presence of these risks, and long term conflicts related to land-grabbing and resource theft linked to said development, has in some cases strengthened community ties and increased capacity for active resistance. While some Mebengokrê (Kayapó) communities in the Amazon have fled further into the forest to maintain isolation, others have expelled gold-miners from their villages. Tupinambá and Pataxó communities in the Northeast have set up blockades to keep people, and the virus, out. The retomadas, or reclaiming of land, of the Tupinambá, Pataxó and Pataxó-Hãhãhai in Bahia State, are a case in point: the long-term struggle to reclaim their lands has strengthened community ties and capacity for active resistance. The recent road blockades of the Mebengokrê (Kayapó) incorporated demands for COVID-19 support into a long history of demands for compensation for the negative impacts suffered from mining and road construction in their territories. At the national level, indigenous movements, which have grown in strength and number in the fight against Bolsonaro's 'politics of extermination' and through engagement of a new cohort of indigenous youth who had access to higher education, were able to draw on social media and indigenous led court cases to help counteract the 'genocide by omission' that has been worsened by the pandemic.